Perbandingan Puisi â€œDoaâ€ Karya Chairil Anwar dan â€œTuhankuâ€ Karya Herawati Mansur - Sti M, Ratri; Wulandari, Yosi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is motivated by the similarity of themes in the reading of Chairil Anwar's "Doa" poem and Herawati Mansur's "God" poem. The purpose of this study was to describe the similarities and differences between the two poems. The method used in this research is comparative descriptive. The data sources used are "Doa" by Chairil Anwar and the poem "My God" by Herawati Mansur. This study uses an intertextuality approach. The results of this study found similarities between the two poems, including the theme of divinity, using the same diction, using hyperbole, and there are similarities in meaning in the poetry lines. While the difference between the two poems is the difference in title, the line in the poem "Doa" is 16 lines while in the poem "My Lord" there are 18 lines. In addition, the messages in the two poems are also different. In the poem "Doa" has a mandate to invite readers to reflect and live life. Meanwhile, the poem "My God" has a mandate that we as creatures must always obey and have faith in God.